Au nanoparticle@hollow mesoporous carbon with FeCo/graphitic shell nanoparticls as a magnetically recyclable yolk–shell nanocatalyst for catalytic reduction of nitroaromatics - Yonghoon Hong (Nature Portfolio, 2018)
Abstract We have developed a highly stable and magnetically recyclable yolk–shell nanocatalyst for catalytic reduction of nitroaromatics. This nanocatalyst is composed of a ~13 nm Au nanoparticle encapsulated in a hollow mesoporous carbon (hmC) shell with a diameter of ~120 nm and a thickness of ~15 nm. The hmC shell contains ~6 nm FeCo/graphitic carbon shell (FeCo/GC) nanoparticles. We have synthesized the Au@hmC-FeCo/GC nanocatalyst by thermal decomposition of Fe and Co precursors in silica of a solid core/mesoporous shell structure containing a Au nanoparticle within the core, subsequent ethylene chemical vapor deposition (CVD), and then removal of the silica by treatment with aqueous HF. The Au@hmC-FeCo/GC has superparamagnetism and high saturation magnetization (29.2 emu g−1) at room temperature. It also shows a type IV sorption isotherm, typical for mesoporous carbon (pore diameter = 3.5 nm), thereby ensuring ready accessibility to the Au core by substrates. We have shown that the Au@hmC-FeCo/GC catalyses the reduction of 4-nitrophenol and 4-nitrotoluene more efficiently than Au nanoparticles do, can be separated very quickly from the reaction mixture using an magnet, and can be reused for the same reduction reaction at least five times without loss of the initial level of catalytic activity.